Managing Financial Flows In The Public Sector Through Digital Transformation - Nadela Lastanti; Mohamad Djasuli (Eduvest - Journal of Universal Studies, 2024)
This article analyzes digital transformation in public financial management in the digital era, focusing on challenges, strategies, and recommendations to address these changes. The method used in this research is descriptive qualitative with a historical research approach. Various strategies, such as the implementation of integrated financial information systems and e-procurement, have been developed to enhance efficiency and transparency in public financial management. However, challenges such as inadequate technological infrastructure, limited human resources, and cybersecurity risks remain key issues that need to be addressed. Recommendations for increasing investment in technological infrastructure, technical skills training, and cross-sector collaboration are suggested to ensure the successful digital transformation of public financial management in the future. It is hoped that these collective efforts will bring significant benefits in improving public financial governance, providing better services to the public, and promoting sustainable economic growth.